KEPEMIMPINAN KEPALA MADRASAH PEREMPUAN DALAM MEWUJUDKAN MADRASAH MANDIRI BERPRESTASI - Saiful Akhyar Lubis, Amiruddin Siahaan, Nur Aisyah Rahma Siregar (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This research was conducted in State Islamic Madrasahs throughout the city of Medan with the aim of seeing what strategies were carried out by the female Heads of State Islamic Madrasahs in realizing the madrasa slogan from the Ministry of Religion in 2021, namely Madrasah Mandiri Berprestasi. The research approach used in this research is descriptive qualitative research. So the procedure of this research, will produce descriptive data, in the form of written or spoken words from people and observable behavior. This qualitative descriptive research aims to detect a situation or phenomena as they are. The type of descriptive research used in this research is case study research. Case study research is a research that is conducted intensively in detail and depth on a particular organization, institution or phenomenon. The results of this study include:First. The work program of female madrasah principals. At this point, each madrasah principal is obliged to compile the performance of the madrasah head, the performance must be in accordance with the needs of the madrasa in order to realize an independent madrasa with achievement. Second. The components of madrasa independence, namely madrasas must be able to be financially independent and independent in learning. Third. The component of achievement, the achievements of women leadership at madrasah ibtidaiyah throughout the city of Medan, is the realization of environmentally-based madrasas, so that many madrasas led by a woman have won Adiwiyata starting from the Municipal level to the National level.